A Cost Analysis of the U.S. Air Force Overseas Posture Informing Strategic Choices - Mills, Patrick (RAND Corporation, 2013)
This report seeks to inform the debate over the extent of U.S. military presence overseas by providing a rigorous estimate of the costs associated with maintaining U.S. Air Force installations and units overseas rather than in the United States.